1990
DOI: 10.1016/0735-1097(90)92837-r
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of supravalvular aortic stenosis and pulmonary artery stenosis

Abstract: Data from 35 patients with supravalvular aortic stenosis or pulmonary artery stenosis, or both, undergoing cardiac catheterization between 1973 and 1989 were analyzed retrospectively. Twenty-seven patients had supravalvular aortic stenosis: 11 required surgery after the first investigation and 8 (80%) of 10 others undergoing serial investigation showed an increase in the left ventricle to aorta pressure gradient. Angiographic measurements showed that the increase in the aortic pressure gradient was related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 10 publications
3
66
0
2
Order By: Relevance
“…3,29 Although mortality improved in the second half of this series, the incidence of complications remains significant. This finding, coupled with the possibility of spontaneous improvement has caused us to recommend frequent noninvasive observation in the asymptomatic infant or young patient with subsystemic RV pressure who does not have significant left-sided involvement.…”
Section: Intervention Versus Observationmentioning
confidence: 89%
“…3,29 Although mortality improved in the second half of this series, the incidence of complications remains significant. This finding, coupled with the possibility of spontaneous improvement has caused us to recommend frequent noninvasive observation in the asymptomatic infant or young patient with subsystemic RV pressure who does not have significant left-sided involvement.…”
Section: Intervention Versus Observationmentioning
confidence: 89%
“…16 The natural history of PAS in WS is one of improvement, which has been described in multiple studies. 16,37,38 This natural history is likely related to the change in arterial medial tension that occurs in the postnatal period. Pulmonary arterial concentrations of elastin normally decrease in the first few months of life, at a time when pulmonary vascular resistance is normalizing.…”
Section: Pulmonary Arterial Stenosismentioning
confidence: 99%
“…8 The association between SVAS and PPS is well recognized 1 and experience with children and adolescents has shown that in untreated patients, the degree of left ventricular outflow obstruction increases with age, whereas the associated PPS may become less severe 2,3,10 because of an increase in thes systolic distensibility of the pulmonary artery rather than to true luminal growth. 3 The same natural course occurred in the case; that is, regression of the PPS with reduction of right ventricular pressure, together with apparent progression of SVAS. Because of the progressive nature of SVAS, surgical treatment was recommended, either a standard patch aortoplasty or extended aortoplasty.…”
Section: Discussionmentioning
confidence: 61%
“…1 Further, its association with peripheral pulmonary stenosis (PPS) is well known. 2,3 A straight thoracic spine, with compression of the heart and great vessels by the chest deformity, has been designated as 'straight back syndrome' and it simulates organic heart disease by causing systolic murmurs and alterations of heart sounds in patients with a normal heart. 4,5 We present a rare case of SVAS and PPS with a straight thoracic spine.…”
mentioning
confidence: 99%